Natural resources - Burrud, John; Chow, Valerie; Horton, Drew; Soto, Richard; Walker, Jim; Schlessinger Media; Burrud Productions (Wynnewood, PA: Schlessinger Media, 2000)
Students will examine about renewable and nonrenewable resources, touching in their sources and uses. Discover the best methods of conserving nonrenewable resources.
Keywords: Natural resources; Conservation of natural resources; Earth sciences